Hubungan Peran Kelompok Tani dengan Produksi dan Pendapatan Usahatani Jagung di Desa Bumi Agung Jaya, Buay Rawan Ogan Komering Ulu Selatan - Sriati, Sriati; Santri, Zadila (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Sriati, S., & Santri, Z. (2023). Correlation between the role of farmer groups and corn farming production and income in Bumi Agung Jaya Village, Buay Rawan Ogan Komering Ulu Selatan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 696-705). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Farmer groups are groups of farmers who are bound non-formally and are formed on the basis of similar interests, similar environments (social, economic, resources), familiarity and harmony and have leadership to achieve common goals. The research objectives are: (1) measuring the level of group role farmers in corn farming (2) calculating the production and income of farmers from corn farming, and (3) analyzing the correlation between the role of farmer groups and the production and income of corn farming. The research was conducted in Bumi Agung Jaya Village, Buay Rawan District, South OKU Regency, using a survey method. Sampling is carried out in stages. The population consists of 176 farmers who are members of Gapoktan Tani Agung, which consists of 7 farmer groups. Samples were taken randomly from each group of 6 farmers, so the total sample was 42 farmers. Data consists of primary and secondary data. The data was processed tabulatedly and analyzed descriptively, and analysis of correlation between the role of farmer groups and production and income was carried out using the Spearman Rank Correlation Test. The results of this research show that the role of farmer groups is included in the medium category, there is a significant correlation between the role of farmer groups and production, value Rs=0.546**, and correlation between the role of farmer groups and income, value Rs= 0.589**. and correlation between production and farmer income is Rs = 0.93**, significant at a =0.01.